High enrichment and ultra-trace analysis of aflatoxins in edible oils by a modified hollow-fiber liquid-phase microextraction technique. Issue 64 (26th July 2017) - Huang, Siming; Chen, Xiao; Wang, Ying; Zhu, Fang; Jiang, Ruifen; Ouyang, Gangfeng
Abstract : An improved hollow-fiber liquid-phase microextraction approach with excellent purification and enrichment capabilities enabled the method have good potential for future ultra-trace analysis of AFTs. Abstract : An improved approach for the ultra-trace analysis of aflatoxins B1, B2, G1 and G2 in edible oils was developed for the first time by a hollow-fiber liquid-phase microextraction (HF-LPME) technique. Good linearity, low limits of detection, high enrichment factors and good repeatability were obtained, which ensured the application of the method for ultra-trace detection of AFTs in edible oils.